(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
As per Indian Philosophy, Anna or nourishment is a part of Brahman. It is a blessing from Paramatma. In this way, it ought to be treated with incredible regard. The physical body is called Annamaya Kosha, for example sustenance body, since body supported and develops by engrossing the energies from nourishment. Sustenance ought to be eaten for the survival and quality of the body, however not for joy. Fasting is another part of customary nourishment framework. It is intended to clean the brain and the body. These conventional nourishment ideas have been changed radically in our general public in view of our contemporary way of life. The different parts of conventional sustenance framework has been recorded in old sacred texts, writing and just as in oral accounts of people. We may discover unique nourishment things and numerous dietary assortments in Karnataka. These assortments have various minimal utilized exceptional vegetables with saw medical advantages. Key conventional staple nourishment and other nutrition classes, for example, nuts, seeds, wild foods grown from the ground utilized in the eating routine are territory explicit. Customary sustenance framework assumes a noteworthy job in keeping up the prosperity and strength of Indigenous People. However, proof proliferates demonstrating that the conventional nourishment base and learning of Indigenous People are being disintegrated.. Mindfulness made on customary sustenance framework can add to make a solid society to assemble solid country. The conventional learning of sustenance is viewed as the best for specific topographical condition. Changing sustenance example can harm the great strength of the general public. Thus, it is imperative to know the significance of good nourishment propensities for our own convention and adjusted eating regimen. In this part, significance of customary nourishments like staple, extraordinary, occasional, district explicit and their techniques will be examined.